Natural convection in porous triangular enclosures with a solid adiabatic fin attached to the horizontal wall - Varol, Yasin; Öztop, Hakan Fehmi; Varol, Asaf (Pergamon-Elsevier Science Ltd, 2007)
A numerical analysis has been performed to investigate the effects of fin location onto the bottom wall of a triangular enclosure filled with porous media whose height base ratio is 1. The temperature of the bottom wall is higher than that of the inclined wall while the vertical wall is insulated. Thus, the fin divides the heated bottom wall to two separate regions. Finite difference method was applied to solve governing equations which are written using Darcy method. Solutions of algebraic equations were made by Successive Under Relaxation (SUR) technique. The effective parameters on flow and temperature fields are: Rayleigh number, location center of fin, dimensionless fin height, and dimensionless fin width. The obtained results indicated that the fin can be used as a control element for heat transfer and fluid flow. (c) 2006 Published by Elsevier Ltd.
Keywords: porous media; triangular enclosure; fin; natural convection